Patterns of noncicatricial alopecia in children: a cross-sectional study - Essam Elden M. Mohamed; Hazem L. Abdel-Aleem; Yara T. Tawfik (Al-Azhar Assiut Medical Journal)
Background and aim Hair loss in children is an unpleasant complaint. It represents a challenge for the treating physician, is extremely upsetting to the parents, and has a psychosocial complication for the growing child. Our study aims to clarify the causes and forms of noncicatricial alopecia in a sample of pediatric patients and to identify the common trichoscopic features of each illness. Patients and methods This study was conducted on 300 children who attended the outpatient dermatology clinics at Al-Azhar University in Assiut. Their ages ranged between 2 and 18 years old and they complained of scalp disorder and hair loss. Results Tinea capitis (TC) was the most common form of pediatric alopecia (136 patients, 45%), while alopecia areata (AA) and marginal traction alopecia were the second most common causes with a frequency of 57 (19%) and 56 (18.7%), respectively. Toxic alopecia was identified in 30 (10%) of the patients, telogen effluvium in 11 (3.7%), while six (2%) patients presented with female pattern hair loss, three (1%) patients had short anagen syndrome and only one patient presented with Trichotillomania. The most common trichoscopic features in patients who had TC were comma hair and short, broken hair, while microexclamation marks were the most common trichoscopy features among AA patients. Conclusion TC was the most common cause of pediatric alopecia, followed by AA and marginal traction alopecia. Diagnosis of hair and scalp disorders enhances the diagnostic power beyond basic clinical examination and exposes unique aspects of the diseases, leading to better management.